Quality and risk in contemporary U.S television - Strouther, Danielle (2017)
This dissertation explores the terms quality and risk in U.S television in the TVIV (2007-present) era. It defines the two terms, what their relationship is to each other and how they are used within television discourse and industry. By arguing that quality television is fundamentally associated with risk, this project will contribute new knowledge and areas of discussion into quality literature by outlining the importance of risk within quality television and the relationship between the two terms. This dissertation uses a combination of textual analysis and media industries methodologies to identify different types of risk in quality television. It explores how risk emerges not only within the content of a show but also through elements such as the show’s commissioning, distribution and audience. The project looks at three different contexts of quality television, using the case studies of Game of Thrones (2011-) for the premium cable company HBO, House of Cards (2013-) for the VOD service Netflix and Crazy Ex Girlfriend (2015-) for the broadcast network The CW. The three different contexts show how risk can originate from different sources, such as from critics or from the company itself, and have positive or negative connotations which serve specific purposes, such as a promotion or lessening a potential challenge from competing programmes or companies. Through the case studies, this project outlines a complex and fluid relationship between quality and risk, in which the quality label can frame the way risk is perceived in positive or negative ways. In addition, this dissertation also argues that if the levels of risk go beyond an implied accepted level, the show holds a negative association of risk and can lose its status of quality. Overall, this dissertation argues that risk is a fundamental part of quality television and the two terms must exist in tension for a television show to be perceived as quality.